2014
DOI: 10.1523/jneurosci.0747-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Neural Control of Vascular Reactions: Impact of Emotion and Attention

Abstract: This study investigated the neural regions involved in blood pressure reactions to negative stimuli and their possible modulation by attention. Twenty-four healthy human subjects (11 females; age ϭ 24.75 Ϯ 2.49 years) participated in an affective perceptual load task that manipulated attention to negative/neutral distractor pictures. fMRI data were collected simultaneously with continuous recording of peripheral arterial blood pressure. A parametric modulation analysis examined the impact of attention and emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 46 publications
4
29
0
Order By: Relevance
“…In line with previous evidence that suggests that emotion and executive functions share neural processes [Ochsner et al, ; Okon‐Singer et al, , ; Rohr et al, ], our conjunction analysis found STS and IPL to be involved in both the prioritization of either positive or negative cues and subjective conflict evaluation. Greater activity in the STS correlated with subjectively evaluating a conflict as less intense, and also correlated with prioritizing positive over negative cues during the scenes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with previous evidence that suggests that emotion and executive functions share neural processes [Ochsner et al, ; Okon‐Singer et al, , ; Rohr et al, ], our conjunction analysis found STS and IPL to be involved in both the prioritization of either positive or negative cues and subjective conflict evaluation. Greater activity in the STS correlated with subjectively evaluating a conflict as less intense, and also correlated with prioritizing positive over negative cues during the scenes.…”
Section: Discussionsupporting
confidence: 91%
“…However, it is not yet clear how neural underpinnings differ when positive or negative cues are prioritized regardless of the modality in which they are presented. In addition, accumulating evidence suggests that emotion and executive functions are inherently linked [Ochsner et al, ; Okon‐Singer et al, , ; Rohr et al, ], highlighting the possibility that conflict evaluation, an executive process, and valence prioritization, an emotion process, may rely on shared neural processes.…”
Section: Introductionmentioning
confidence: 99%
“…Converging with other work focused on emotion-related distraction (Bishop, 2007; Etkin, 2012; Bishop and Forster, 2013; Etkin et al, 2013; Okon-Singer et al, 2014a; van Ast et al, 2014), they suggest that degraded performance reflects two processes: (a) increased engagement of regions involved in processing socio-emotional information and orchestrating emotional expressions (e.g., amygdala), and (b) a reduction of delay-spanning activity in frontoparietal cortex.…”
Section: How Does Emotion Influence Cognition?mentioning
confidence: 58%
“…The results demonstrated that among healthy individuals, neurocognitive attention mechanisms modulate BP and neural reactions to aversive stimuli in a network that includes prefrontal, parietal, limbic and brainstem regions previously shown to be related both to emotion control and to BP reactivity. Gupta () suggested that the decline in BP levels shown by Okon‐Singer et al () is due to activation of feedback mechanisms in brain regions associated with emotional processing (Gupta, ). In our study, similar mechanisms may have caused the BP decrease in response to negative‐valenced pictures.…”
Section: Discussionmentioning
confidence: 99%
“…The pictures were chosen according to valence ratings based on International Affective Norms for participants. Eighty pictures had negative valences ( M : 2.35, SD : 0.84) and 80 pictures had neutral valences ( M : 5.13, SD : 0.51), based on Okon‐Singer et al (). No differences were found between negative and neutral pictures in visual features such as luminance, contrast or dominant spatial frequency.…”
Section: Methodsmentioning
confidence: 99%